Improving the performance of a biofuel cell cathode with laccase-containing culture supernatant from Pycnoporus sanguineus. (January 2015) - Fokina, Oleksandra; Eipper, Jens; Winandy, Lex; Kerzenmacher, Sven; Fischer, Reinhard
Highlights: Easy to produce high redox laccase from Pycnoporus sanguineus . Using crude culture supernatant of Pycnoporus sanguineus in biofuel cells. Laccase in culture supernatant improves cathode performance under different pH values. Abstract: Laccases are multicopper oxidoreductases that can be used in biofuel cells to improve cathode performance by cathodic oxygen reduction. Here we present a laccase from the ligninolytic white-rot fungus Pycnoporus sanguineus that, in contrast to the Trametes versicolor laccase, can be produced in the absence of inducers in a standard culture medium. After 7 days of cultivation the activity of this laccase in culture supernatant reached 2.5 U/ml, which is high enough for direct application of the supernatant in biofuel cells. The highest current density of 115.0 ± 3.5 μA/cm 2 at 400 mV vs. SCE was obtained at pH 5 with a buckypaper cathode with a laccase-containing culture supernatant. The enzyme also showed electrocatalytic activity at pH 6 and 7. These results not only present a new cost-efficient laccase for improving cathode performance, but also show that new laccases with different catalytic properties can be suitable for biofuel cells.